Implementation of Discovery Learning Models to Improve Understanding of Soci-Cultural Change Material at SMP Negeri 02 Rumbia, Indonesia - Arisland Arisland (USN Scientific Journal, 2023)
This study aims to increase understanding of the material on socio-cultural change in class IX at SMP Negeri 02 Rumbia through the application of the Discovery Learning model. This research is a Classroom Action Research (CAR) which is carried out in three cycles, with each cycle consisting of planning, action, observation, and reflection. The research subjects were class IX students of SMP Negeri 02 Rumbia. Sources of data are teachers and students. Data collection techniques through observation and written tests, then analyzed using descriptive qualitative. Based on the results of the study, it can be concluded that the efforts made to increase students' understanding are by applying the discovery learning learning model. showed an increase but still below the success criteria but finally in cycle III an average of 90.97 was obtained indicating the Very Good category. Obtained student learning outcomes in the material 'Socio-cultural changes' increased from cycle I to cycle III, as well as the percentage of students who achieved mastery learning increased from cycle I obtained an average learning result of 72.22 with learning completeness of 61% increased in cycle II obtained an average learning result of 79.17 with a complete learning of 75% and the last increase in cycle III obtained an average learning result of 89.72 with a learning mastery of 100% showing results that were as expected and showed a significant increase.